The Effect of Six Weeks of TRX Training on Selected Physical Fitness Components in High School Students in Mashhad - Seyed Mojtaba Tabatabai Asl; Parvin Jalilian (Biyumikānīk-i varzishī)
Objective Physical fitness is an essential component of daily activities and is widely recognized as a key indicator for evaluating students' functional performance. This study aimed to examine the effect of six weeks of TRX suspension training on selected physical fitness components in high school students. Methods This semi-experimental, applied study was conducted in a field setting. The statistical sample consisted of 40 tenth-grade male students from a secondary school in Mashhad. Participants were randomly assigned to either a training group or a control group, with 20 students in each. The stork balance test was used to assess static balance; the modified pull-up test evaluated upper body muscular endurance; and the standing long jump and sit-and-reach tests measured lower limb power and hamstring flexibility, respectively. The training group followed a TRX suspension training program for six weeks, three sessions per week, with each session lasting 60 minutes. Results The results revealed significant improvements in balance, muscular endurance, and flexibility in the training group compared to the control group. However, no significant difference was observed between the groups in terms of lower limb power. Conclusion Overall, TRX suspension training appears to enhance endurance, balance, flexibility, and neuromuscular control of the core stabilizing muscles. Based on these findings, it is recommended that school physical education instructors incorporate TRX-based suspension training into their programs to improve various aspects of students’ physical and anthropometric fitness.